Analisis Peran Vitamin C pada Pigmentasi Kulit - Rosa Adelia Anhar; Sovy Maendah Cahyaningsih; Vara Aurel Rania; Zulalina Qurratu Aini Syukur; Liss Dyah Dwi A (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
The skin's primary function is to act as a barrier against environmental insults, and its unique structure reflects this. The skin consists of two layers: the outer epidermis layer is highly cellular and provides a barrier function, and the inner dermal layer ensures strength and elasticity and provides nutritional support to the epidermis. Normal skin contains high concentrations of vitamin C, which supports important and well-known functions, stimulates collagen synthesis and aids in antioxidant protection against UV damage. This knowledge is often used as a rationale for adding vitamin C to topical applications, but the efficacy of such treatment, compared with optimizing dietary vitamin C intake, remains poorly understood. This review discusses the potential role of vitamin C in skin health and summarizes in vitro and in vivo research to date. We compare the efficacy of vitamin C nutritional intake versus topical application, identify areas where a lack of evidence limits our understanding of the potential benefits of vitamin C on skin health, and suggest which skin properties are most likely to benefit from increased vitamin C nutrition. that the effect of vitamin C on pigmentation has positive results, namely brightening the skin. several treatments for pigment disorders, in this case the management of melasm and lentigo senilis using vitamin C for systemic treatment.